SUSTAINABLE USE OF MEDICINAL AND AROMATIC PLANTS FROM THE FOREST ECOSYSTEMS LOCATED IN DOGROGEA (SOUTH-EASTERN ROMANIA) - Diana VASILE; Maria DINCĂ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The tradition of using medicinal and aromatic plants in Romania dates back to the year 1862. The purpose of the present paper is to identify the main medicinal and aromatic plants, as well as estimating the quantities that can be harvested from Dobrogea in 2018 from the forest fund managed by RNP - Romsilva, the National Forest Management Institute. As such, 21 medicinal plants were identified in the two forest districts (DS) from Constanța and Tulcea Counties. A quantity of 22 t of medicinal plants from 10 species was estimated for harvesting in DS Constanța, while in DS Tulcea the number reached 588 tones from 21 species. The largest quantities that can be harvested in DS Constanța are represented by locust (Robinia pseudoacacia) – 5 tones and elderberry (Sambucus nigra) – 5 tones, while for DS Tulcea they are represented by silver linden (Tilia tomentosa) – 180 tones, elderberry (Sambucus nigra) – 60t and nettle (Urtica dioica) – 50 tones. All the other species can be gathered in quantities ranging from 1 ton to 40 tones. Taking into account the natural conditions, Dobrogea region is characterised by a high potential of medicinal plants. The possibility that these natural resources are maintained and even developing future abundant populations is conditioned by the appliance of appropriate management measures that abide to the present laws, the species sustainability principle as well as the protection of endangered species.